PREFERENSI KONSUMEN TERHADAP PEMBELIAN BUAH PEPAYA (Carica papaya L) DI PASAR TRADISIONAL GIWANGAN KOTA YOGYAKARTA - Taufik, Muhammad; Hartawaty, Dheny Arina (Fakultas Pertanian, Universitas Janabadra, 2024)
Consumers have preferences that must be understood by producers, sellers, and marketers, as these preferences influence consumer likes and dislikes. Consumer preferences for the attributes of papaya (Carica papaya L) aim to determine the most preferred attributes by consumers in the Giwangan traditional market. The research was conducted using survey techniques, interviews, and questionnaires. The research location was deliberately chosen at the Giwangan fruit and vegetable traditional market due to the consideration that it is the main fruit market in the city of Yogyakarta. The researcher took a sample of 32 respondents. The analysis used is the chi-square analysis. The chi-square analysis shows that consumer preferences for papayas at the Giwangan market are for papayas that have a sweet taste, a skin color with a yellow blush, a firm flesh texture, and a medium sized fruit.